Word recognition through Malay animal fables - Sujud, Arba'ie; Abd Rahim, Normaliza; Nik Muhamad Affendi, Nik Rafidah (Canadian Center of Science and Education, 2014)
The study focuses on the word recognition using the Malay Animal Fables (MAF) among primary school learners. The objectives of the study were to identify and discuss the words (noun, adjective and verb) from six animal fables. The MAF were taken from the Malay Folklore program. The samples of the study were 100 subjects from two classes of Malay language classrooms. The subjects were picked at random and were interviewed based on the MAF program. The program was based on the stories in the form of songs and the song lyrics. The answers from the subjects were collected and the data were accumulated and anaysed accordingly. The results revealed that the subjects were able to storytell the stories, identify the words and divided the words into noun, adjective and verb. It is hoped that future study will focus on the use of MAF in writing essay.